Real-time screening tool for identifying post-traumatic stress disorder in facial trauma patients in a UK maxillofacial trauma clinic. Issue 11 (November 2021) - Howson, K.; Yeung, E.; Rayner, L.; Fan, K.
Abstract: Post-traumatic stress disorder (PTSD) is a distressing consequence of a traumatic event associated with an increased suicide risk and reduced quality of life. Surgeons often have low confidence in identifying psychological problems. The prevalence of PTSD following facial trauma ranges from 23% to 41%. This highlights the importance of identifying and managing at-risk patients to optimize both mental and physical recovery. IMPARTS (Integrating Mental and Physical healthcare: Research, Training and Services) provides electronic screening tools to guide the non-mental health clinician in the 'real-time' identification, documentation, and management of potential mental health problems. The bespoke IMPARTS facial trauma screening tool was piloted in a UK oral and maxillofacial surgery trauma clinic from July 2015 to November 2017. A total of 199 patients completed screening, with 48 (24%) screening positive for possible PTSD. Further analysis of these 48 patients revealed that four (8%) had PTSD symptoms alone; three (6%) also screened positive for depression, 17 (35%) for co-existing symptoms of anxiety, and 24 (50%) for PTSD, anxiety, and depression. IMPARTS was found to be a highly effective tool aiding the non-mental health clinician to screen for PTSD and initiate prompt management. The data captured informs planning of the psychological support service.